Analysis of Laser Sintered Materials Using Finite Element Method - Ahmad Shahir, Jamaluddin; Abdullah, Yassin (Penerbit Universiti Kebangsaan Malaysia, 2013)
Invention of milling combined laser sintering system (MLSS) is able to reduce the mould manufacturing time and improve the mould accuracy. Thus, more study is needed to increase the understanding for the laser sintered material machining characteristic to gain benefit from the invention of MLSS. This paper clarified the analysis of laser sintered material machinability with the application of Finite Element Method (FEM). Mild steel AISI1055 was applied in developing the Finite Element model in this study due to its popularity in machinability test and adequate level of data vailability. 2D orthogonal cutting was employed on edge design tools with updated Lagrangian coupled thermo mechanical plane strain model. Adaptive meshing, tool edge radius and various types of friction models were assigned to obtain efficient simulations and precise cutting results. Cutting force and cutting-edge temperature estimated by Finite Element Method are validated against corresponding experimental values by previous researchers. In the study, cutting force increases when radial depth increases and lowest error acquired when the shear friction factor of 0.8 was applied. Machining simulation for laser sintered materials estimated lower cutting force compared with mild steel AISI1055 due to lower Young modulus. Higher cutting temperature estimated for machining simulation laser sintered material compared with machining simulation mild steel AISI1055 due to its low thermal conductivity